Exploring the Relationship Between Value Modularity, Knowledge Transfer, and Firm Innovation Performance: Evidence From China - Wang, Jianhua; Zhao, Yan; Han, Xiao; Li, Luying; Rasool, Samma Faiz (Frontiers in Psychology, 2022)
This study aims to explore the influence the value modularity and firm’s innovation performance, directly and indirectly, using knowledge management as mediating variable. Moreover, in this study we used the resource integration ability as moderator between the relationship value modularity and firm innovation performance. Based on prospect theory and information comparison theory, in this paper, we used the archival data related to high-tech firms of state-owned and state-controlled from China statistics Yearbook on High Technology Industry. The outcomes of this study indicate that value modularity and firm innovation performance has inverted U-shaped and significant association. Similarly, results also confirm that knowledge acquisition and knowledge internalization mediates the relationship between value modularity and firm innovation performance. The finding of this research also confirm that resource integration ability negatively effect the relationship between value modularity and firm innovation performance. This paper enriches the research of the value modularity and gives certain inspiration to knowledge management. At the end of this study we also suggest some significance practical implications.